A stepping stone perspective to detection of network threats - Omar, Mohd Nizam; Amphawan, Angela; Din, Roshidi (North Atlantic University Union, 2013)
Current computing trends such as cloud computing, file sharing and social networking promote collaboration and allow greater mobility for users.Nevertheless, these computing trends increase the vulnerability of networks to security threats and challenge network resources.An ingenious technique employed by attackers for retaining anonymity is by exploiting intermediary host computers or stepping stones to instigate attacks on other computers.This paper explores novel application of the stepping stone detection concept in addressing network threats such as spams, backdoors, proxy server intrusions and denial of service attacks.Preliminary stepping stone detection models for each security threat will be constructed and the potential detection process is delineated.These preliminary concepts and models may prove useful for further optimization of network security in conjunction with other conventional detection techniques.